Menempuh Ujian Biomedis : Persiapan dan Cara-Caranya - T. Jacob, T. Jacob (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1980)
This article discusses the aims and various kinds of biomedical examinations and their evalua Ã¢â¬Â¢ Lion, primarily to assist those preparing for such undertakings. Among those aims, examination as a measure for protection of the public against incompetence and for quality control seems to be gradually disemphasized.Practical hints and